Schedulability Analysis for Rate Monotonic Algorithm-Shortest Job First Using UML-RT. (23rd July 2014) - Pon Pushpa, S. Ewins; Devasikamani, Manamalli
Abstract : System modelling with a unified modelling language (UML) is an active research area for developing real-time system development. UML is widely used modelling language in software engineering community, to specify the requirement, and analyse the target system successfully. UML can be used to provide multiple views of the system under design with the help of a variety of structural and behavioural diagrams at an early stage. UML-RT (unified modelling language-real time) is a language used to build an unambiguous executable specification of a real-time system based on UML concepts. This paper presents a unified modeling approach for a newly proposed rate monotonic scheduling algorithm-shortest job first (RMA-SJF) for partitioned, semipartitioned and global scheduling strategies in multiprocessor architecture using UML-RT for different system loads. As a technical contribution, effective processor utilization of individual processors and success ratio are analyzed for various scheduling principles and compared with EDF and D_EDF to validate our proposal.